Multicentric Standardization of Protocols for the Diagnosis of Human Mitochondrial Respiratory Chain Defects - Nuria Bujan; Constanza Morén; Francesc J. García-García; Alberto Blázquez; Clara Carnicer; Ana Belén Cortés; Cristina González; Ester López-Gallardo; Ester Lozano; Sonia Moliner; Laura Gort; Ester Tobías; et al. (MDPI AG, 2022)
The quantification of mitochondrial respiratory chain (MRC) enzymatic activities is essential for diagnosis of a wide range of mitochondrial diseases, ranging from inherited defects to secondary dysfunctions. MRC lesion is frequently linked to extended cell damage through the generation of proton leak or oxidative stress, threatening organ viability and patient health. However, the intrinsic challenge of a methodological setup and the high variability in measuring MRC enzymatic activities represents a major obstacle for comparative analysis amongst institutions. To improve experimental and statistical robustness, seven Spanish centers with extensive experience in mitochondrial research and diagnosis joined to standardize common protocols for spectrophotometric MRC enzymatic measurements using minimum amounts of sample. Herein, we present the detailed protocols, reference ranges, tips and troubleshooting methods for experimental and analytical setups in different sample preparations and tissues that will allow an international standardization of common protocols for the diagnosis of MRC defects. Methodological standardization is a crucial step to obtain comparable reference ranges and international standards for laboratory assays to set the path for further diagnosis and research in the field of mitochondrial diseases.